The reform of the justice system as a public policy: have we already found the right path? - Vargas Guevara, Erick Eduardo (Universidad Nacional del Litoral, 2019)
In this paper we state that the justice system’s reform must be considered as a public policy. This necessarily implies the Government performing actions to solve the Peruvian justice system’s defects and problems. In this sense, we assume that not only does the justice system comprise the Judiciary, but also every other entity where the citizen can find a solution to his conflicts or legally relevant problems (Ministerio Público, Instituto de Medicina Legal, RENIEC, SUNARP, among others). Thus, not only is the Government’s role in the system’s reform limited to approving rules or declaring principles, but also must be materialized in actions from a dynamic point of view. Precisely, in our paper we formulate some actions the Government must carry out to protect the access to justice of people in circumstances in which structural barriers hinder them from exercising their rights. To this effect, we analyze critically the CERIAJUS and CCRJ reports and the Peruvian Constitutional Court and Judiciary’s statements.